VSV-EBOV Induces Temporal and Dose-Dependent Transcriptional Responses in Non-human Primates - Pinski, Amanda N.; Maroney, Kevin J.; Marzi, Andrea; Messaoudi, Ilhem (Frontiers in Virology, 2021)
Zaire Ebola virus (EBOV), the causative agent of Ebola virus disease (EVD), is a member of the filoviridae family. EVD is characterized by innate and adaptive immune dysregulation that leads to excessive inflammation, coagulopathy, lymphopenia, and multi-organ failure. Recurrent outbreaks of EBOV emphasize the critical need for effective and deployable anti-EBOV vaccines. The FDA-approved VSV-EBOV vaccine protects nonhuman primates (NHPs) and humans from EBOV when given at a 10-20 million PFU dose. We recently demonstrated that a dose as small as 10 PFU protected NHPs from lethal EBOV infection. Furthermore, 1 PFU of VSV-EBOV protected 75% of vaccinated NHPs. In this study, we performed a comparative transcriptional analysis of the whole blood transcriptome in NHPs vaccinated with doses of VSV-EBOV associated with complete protection (10M PFU), protection with mild EVD (10 PFU) and break-through protection (1 PFU) before and after challenge with a lethal dose of EBOV Makona. Transcriptional findings demonstrated that, regardless of dose, vaccination significantly attenuated the upregulation of genes associated with fatal EVD. Genes involved in T and B cell activation were more highly expressed in groups receiving 10 or 10M PFU than in 1 PFU-vaccinated animals. Furthermore, the singular vaccinated (1 PFU) nonsurvivor exhibited a transcriptional signature distinct from both surviving vaccinated animals and controls that received an irrelevant vaccine. These findings provide additional insight into mechanisms of vaccine-mediated protection and informing public policy on vaccine distribution during outbreaks.